Analisis Keuntungan Usaha Jasa penggilingan Kopi di Desa Tanjung Kari Kecamatan Pulau Beringin Kabupaten OKU Selatan - Aprizon; Aisah; Sudarti (Jurnal Bakti Agribisnis, 2024)
Beringin Island District is one of the sub-districts in South OKU Regency which is a coffee plantation center. The coffee is grown on people's plantations which are managed independently or shared between land owners and farmers. As a potential mainstay, coffee has a contribution as the main source of income for the community, especially those who make a living as coffee farmers, entrepreneurs and coffee traders. A coffee mill is an agro-industry or coffee processing business that operates in the agricultural services sector, which offers coffee grinding services. This coffee milling business is a business that is a service or supporting system for coffee agribusiness. The coffee milling business is a business opportunity that cannot be separated from the financial aspect. As a business or venture, the coffee milling business is certainly expected to make a profit. The objectives of this research are (1). To find out the stages of coffee grinding techniques. (2). Calculating the amount of income from the coffee grinding service business, (3). Analyze the level of profit of the coffee grinding service business. The results show that the ground coffee processing process for the ground coffee grinding service business in Tanjung Kari Village, Pulau Beringin District, South OKU Regency goes through several stages, namely: availability of raw materials, separation of coffee beans (sorting), roasting, cooling, grinding and packaging. The production costs of a coffee grinding service business in one production process are IDR 1,133,000, revenue is IDR 1,750,000 and income is IDR 617,000. The R/C ratio value is 1.54, meaning that for every IDR 1 spent on ground coffee grinding services, it will generate revenues of IDR 1.54. The BEP value for revenue from the ground coffee grinding service business is IDR 316,100 with a revenue achievement value of IDR 1,750,000, the production BEP value is 45 Kg with a production achievement of 250 Kg and a price BEP value of IDR 4,500/Kg with a price achievement of IDR 7,000/Kg which shows that the ground coffee grinding service business in Tanjung Kari Village, Pulau Beringin District, South OKU Regency is financially profitable to develop.